Photometric study and evolutionary state for some newly discovered W UMA systems - Alenazi, M. S.; Elkhateeb, M. M. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
First orbital solution and photometric study for the newly discovered systems V968 CEP, ET CMI, and ES CMI was carried out by means of WD code (windows interface version) based on model atmosphere provided by Kurucz. Our modelling revealed absolute and physical parameters, which show that the primary components in all systems are hotter and more massive than the secondary components. According to the estimated parameters, the evolutionary statuses for all systems were estimated on theoretical mass-luminosity and mass-radius curves. Spectral types of the systems components were adopted using the estimated temperatures. Впервые представлены орбитальные решения и фотометрические исследования недавно открытых систем V968 CEP, ET CMI и ES CMI, выполненные с помощью кода WD (версия интерфейса Windows), на основе моделей атмосфер Куруца. Наше моделирование выявило абсолютные и физические параметры, которые показывают, что первичные компоненты во всех системах более горячие и массивные, чем вторичные компоненты. Согласно рассчитанным параметрам, эволюционные статусы для всех систем оценивались по теоретическим кривым масса-светимость и масса-радиус. Спектральные типы компонентов систем приняты исходя из расчетных температур.
Keywords: Astrophysics